(untitled) (Journal Of Educational and Psychological Researches, 2017)
This study aimed to investigate the effect of fish bone in the of chemistry and self-organized learning for students of the second grade‚ achievement . The study sample consisted of 84 students from the second grade students middel in the of alrasheed boys school, of the Directorate of Educational Karkh II, in two divisions, Division of (a) an experimental group that studied the strategy fish bone, and the Division (d) a control group which studied the usual way. The results indicated the presence of significant differences in favor of the experimental group that studied using the fish bone in achievement and learning self-organized strategy students